2015
DOI: 10.1016/j.dental.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Water distribution in dentin matrices: Bound vs. unbound water

Abstract: Objectives This work measured the amount of bound versus unbound water in completely-demineralized dentin. Methods Dentin beams prepared from extracted human teeth were completely demineralized, rinsed and dried to constant mass. They were rehydrated in 41% relative humidity (RH), while gravimetrically measuring their mass increase until the first plateau was reached at 0.064 (vacuum) or 0.116 g H2O/g dry mass (Drierite). The specimens were then exposed to 60% RH until attaining the second plateau at 0.220 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 55 publications
2
59
0
8
Order By: Relevance
“…Water present in etched dentin keeps collagen fibrils expanded and can be classified as free (unbound) and collagen-bound water. 24 While free water represents approximately 75 to 79% of total water content in demineralized dentin, 21 to 25% is bound water. 24 The application of polar solvents, such as ethanol and acetone may chemically dehydrate dentin, creating a more favorable environment for adhesive infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water present in etched dentin keeps collagen fibrils expanded and can be classified as free (unbound) and collagen-bound water. 24 While free water represents approximately 75 to 79% of total water content in demineralized dentin, 21 to 25% is bound water. 24 The application of polar solvents, such as ethanol and acetone may chemically dehydrate dentin, creating a more favorable environment for adhesive infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…24 While free water represents approximately 75 to 79% of total water content in demineralized dentin, 21 to 25% is bound water. 24 The application of polar solvents, such as ethanol and acetone may chemically dehydrate dentin, creating a more favorable environment for adhesive infiltration. However, Agee et al 24 demonstrated that when applied for 60 seconds on dentin, ethanol and acetone remove respectively, 25 and 34% of unbound water, leaving behind most of the total water content permeating collagen fibrils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerca de 20% a 25% da dentina é constituída de água. A dentina perde cerca de 10% de água após a extração do dente, se este for mantido em ambiente completamente seco em tempo superior a cinco minutos 22 . Os efeitos deletérios sobre a matriz de colágeno e proteoglicano podem atuar como um desencadeador para a contração da dentina, induzindo um aumento da tensão e da propagação de fissuras; além disso, em última análise, podem contribuir para a significativa redução na resistência à fratura 23 .…”
unclassified
“…O conhecimento atual indica que a fratura começa a partir de microfissuras na dentina radicular e estudos laboratoriais têm ligado a sua formação com alguns procedimentos endodônticos de rotina, tais como preparo do canal radicular, obturação e retratamento 22 . Os resultados desta pesquisa contrastam com estudos anteriores, considerando que os defeitos dentinários observados nas imagens após a instrumentação e a secção, na verdade, já poderiam existir no pré-operatório, não sendo, portanto, visíveis ao microspópio.…”
unclassified